2018
DOI: 10.1002/aic.16478
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Thermal model of thermal breakdown in multilayered dielectric elastomers

Abstract: Energy transduction of dielectric elastomers involves minute electrical and mechanical losses, both of which potentially increase the temperature within the elastomer. Thermal breakdown of dielectric elastomers occur when heat generated therein cannot be balanced by heat loss on the surface, which is more likely to occur in stacked dielectric elastomers. In this article an electro‐thermal model of a multilayered dielectric elastomer able to predict the possible number of layers in a stack before thermal breakd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…The elastomer material simulated in this work is a polydimethylsiloxane (PDMS) elastomer, specifically Bluestil RTV 141 from Blustar Silicones 40 , with a thermal conductivity of k 0.16 W/(mK) and a relative permittivity of r 2.7 40 . In our previous work 38 , we found that the electrical conductivity of the PDMS elastomer could be described by an Arrhenius expression with respect to temperature T :…”
Section: Model Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…The elastomer material simulated in this work is a polydimethylsiloxane (PDMS) elastomer, specifically Bluestil RTV 141 from Blustar Silicones 40 , with a thermal conductivity of k 0.16 W/(mK) and a relative permittivity of r 2.7 40 . In our previous work 38 , we found that the electrical conductivity of the PDMS elastomer could be described by an Arrhenius expression with respect to temperature T :…”
Section: Model Setupmentioning
confidence: 99%
“…It should be noted that in Christensen et al 38 , the material used to determine σ Arr was also a PDMS elastomer, but specifically Elastosil RT625 from Wacker Chemie AG.…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum magnitude of the breakdown strength is observed as 132 V/ µm for RT625+ RM130 F at 80°C, which, for this corresponding enhancement, is 43% higher compared to the breakdown value of 92 V/µm at 20°C. At elevated operating temperatures, the thermal conductivity and thermal degradation of the silicone dielectric are crucial in determining the point of thermal breakdown [44]. Furthermore, the maximum breakdown strengths for the RT625+ R420, LR3043+ RM130 F, and LR3043+ R420 systems are observed to be 108 V/µm (40°C), 178 V/µm (50°C), and 174 V/µm (40°C), respectively ( Figure 5), while the maximum corresponding enhancements for the same are found to be 24 %, 16 %, and 6 %, respectively ( Figure 5).…”
Section: Electrical Breakdown Strengthmentioning
confidence: 99%